A new method for modeling district heating systems - Vesterlund, Mattias; Dahl, Jan; Lindblom, Bo; Sandberg, Johan (Luleå tekniska universitet, Energivetenskap, 2012)
Due to the mining of iron ore by the local mining industry (LKAB) a deformation zone is approaching the town of Kiruna, which is situated in the north of Sweden. The town is going through an urban transformation and parts of the town is about to be relocated. The relocating of the town is affecting all the infrastructure of the town, one of those is the district heating system. The aim of this paper is to apply a process integration method to study how the existing district heating system is behaving and to create a model for the whole district heating system.The district heating system in the town has a complex design with several loops. When dealing with modeling of a district heating system there are two methods that are most common, the Danish- and the German methods. These methods allow for simplification of the network shape, still with good accuracy in system behavior compared to real system behavior. A disadvantage with these two methods is that they cannot handle a district heating system that contains loops without making changes compared to the real physical system.A method that allows modeling of loops in the district heating system has been developed, using the remind-software. This method makes it possible to analyze how loops in the district heating system are behaving, without making physical changes when modeling the district heating system. The model will be used as a default model for redesigning the district heating system when moving the town. It will also be used to optimize heat deliveries from LKAB district heating system and for analyzing the possibility for seasonal storage of waste energy from LKAB and municipality energy company TVAB or how new heat production plants should optimized.In this paper the method is described and applied in order to model the whole present district heating system for the town. Godkänd; 2012; 20140305 (matves)